Study Of Low Dimensional Tungsten Oxide By Anodization And Sol-Gel Methods - Chai, Yingqi (2018)
Low dimensional tungsten oxides (WO≤3) have attracted considerable research attention due to potential applications such as electrochromic devices, gas sensors, photocatalysts for water splitting, dye-sensitized solar cells and humidity sensors. The use of tungsten oxide for surface-sensitive device applications requires cost-effective fabrication of tungsten oxide with controllable morphological property. Both anodization and sol-gel methods offer facile ways to synthesize nanostructured tungsten trioxide (WO3).